1997
DOI: 10.1002/lt.500030205
|View full text |Cite
|
Sign up to set email alerts
|

Retransplantation for recurrent hepatitis C

Abstract: Recurrence of hepatitis C virus (HCV) after orthotopic liver transplant (OLT) may be mild or may lead to progressive liver disease requiring retransplantation (re-OLT). Results of re-OLT for hepatitis C are not well known. We analyzed outcomes in 14 patients retransplanted for recurrent hepatitis C. All had evidence of recurrent hepatitis on multiple biopsies. Polymerase chain reaction (PCR) was performed in blood or tissue samples from 12 patients when recurrence was suspected; all 12 were positive for HCV-RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(72 citation statements)
references
References 11 publications
3
68
1
Order By: Relevance
“…As expected, MELD score increased at each interval of evaluation from initial transplantation to reTX. At the time of the first listing and transplantation the MELD scores were higher in group 2 and 3 compared to group 1 (first listing, mean MELD score, 13 [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] vs. 18 vs. 15 ; first transplant, mean MELD score, 15 vs. 20 vs. 18 ). MELD scores at second listing and reTX were distinctly higher than initial listing and transplantation (second listing, mean MELD score, 21 vs. 21 vs. 25 ; reTX, mean MELD score, 26 vs. 25 ).…”
Section: Meld Score Comparisons Among Groupsmentioning
confidence: 82%
See 2 more Smart Citations
“…As expected, MELD score increased at each interval of evaluation from initial transplantation to reTX. At the time of the first listing and transplantation the MELD scores were higher in group 2 and 3 compared to group 1 (first listing, mean MELD score, 13 [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] vs. 18 vs. 15 ; first transplant, mean MELD score, 15 vs. 20 vs. 18 ). MELD scores at second listing and reTX were distinctly higher than initial listing and transplantation (second listing, mean MELD score, 21 vs. 21 vs. 25 ; reTX, mean MELD score, 26 vs. 25 ).…”
Section: Meld Score Comparisons Among Groupsmentioning
confidence: 82%
“…Several single-center studies have noted slightly higher survival than reported by our group. 18,[21][22][23] The reported ability of MELD scores to predict post-reTX survival has been variable. 9,[24][25][26][27] In our study, although MELD scores were not predictive of post-reTX survival, higher MELD scores (particularly Ͼ25) at the time of reTX were associated with high post-reTX mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 We reported severe fibrosing cholestatic hepatitis in 7.4% of patients who underwent liver transplantation for hepatitis C. 5 With longer follow-up, we and others have observed that liver failure and complications of cirrhosis develop as well. 3,17 Once hepatitis C recurs, treatment is largely ineffective. This may be partly because of the extremely high viral levels observed after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Out of a cohort of 12 subjects retransplanted for HCV re-infection, 8 patients have now survived longer than after their first transplant with only mild disease recurrence. 39 This is probably a reflection of the use of less immunosuppression following retransplantation for recurrent hepatitis C.…”
Section: Recurrent Infection Following Liver Transplantationmentioning
confidence: 99%